Implementasi Sistem Pengendalian Internal Pada Sistem Penggajian Koperasi Konsumen Karya Dana Pertiwi Di Denpasar - Ni Komang Sri Septina Dewi; Cokorda Gde Bayu Putra; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2026)
Internal control system is a process that involves all levels of the organization which aims to provide adequate confidence in the achievement of objectives related to operations, reporting and compliance. This research aims to find out how the internal control system for the payroll system at Koperasi Konsumen Karya Dana Pertiwi. The method used in this research is qualitative descriptive analysis, namely analysis carried out by describing and understanding research phenomena based on qualitative data. Data was collected through observation, interviews and documentation. The results of this research found that payroll at Koperasi Konsumen Karya Dana Pertiwi consists of functions, documents and procedures that form unified system. Meanwhile, the internal control system for the payroll system still has dual functions in the control activity component.